Dynamic elements at both cytoplasmically and extracellularly facing sides of the UapA transporter selectively control the accessibility of substrates to their translocation pathway. - Kosti, Vasiliki; Papageorgiou, Ioannis; Diallinas, George (J Mol Biol, 2010)
In the UapA uric acid-xanthine permease of Aspergillus nidulans, subtle interactions between key residues of the putative substrate binding pocket, located in the TMS8-TMS9 loop (where TMS is transmembrane segment), and a specificity filter, implicating residues in TMS12 and the TMS1-TMS2 loop, are critical for function and specificity. By using a strain lacking all transporters involved in adenine uptake (DeltaazgA DeltafcyB DeltauapC) and carrying a mutation that partially inactivates the UapA specificity filter (F528S), we obtained 28 mutants capable of UapA-mediated growth on adenine. Seventy-two percent of mutants concern replacements of a single residue, R481, in the putative cytoplasmic loop TMS10-TMS11. Five missense mutations are located in TMS9, in TMS10 or in loops TMS1-TMS2 and TMS8-TMS9. Mutations in the latter loops concern residues previously shown to enlarge UapA specificity (Q113L) or to be part of a motif involved in substrate binding (F406Y). In all mutants, the ability of UapA to transport its physiological substrates remains intact, whereas the increased capacity for transport of adenine and other purines seems to be due to the elimination of elements that hinder the translocation of non-physiological substrates through UapA, rather than to an increase in relevant binding affinities. The additive effects of most novel mutations with F528S and allele-specific interactions of mutation R481G (TMS10-TMS11 loop) with Q113L (TMS1-TMS2 loop) or T526M (TMS12) establish specific interdomain synergy as a critical determinant for substrate selection. Our results strongly suggest that distinct domains at both sides of UapA act as selective dynamic gates controlling substrate access to their translocation pathway.
Keywords: Adenine; Aspergillus nidulans; Biological Transport; Fungal Proteins; Membrane Transport Proteins; Missense; Mutation; Substrate Specificity